1982
DOI: 10.1016/0014-5793(82)81120-4
|View full text |Cite
|
Sign up to set email alerts
|

Cubic liquid crystalline phase with phosphatidyl‐ethanolamine from Bacillus megaterium containing branched acyl chains

Abstract: Phosphatidylethanolamine(PE) was isolated from membranes of Bacillus megaterium. The organism was grown at 20°C and 55°C. The phase equilibria in PE/water systems were studied by *H and 31P nuclear magnetic resonance, and by polarized light microscopy. PE isolated from B. megaterium grown at 20°C forms a lamellar liquid crystalline phase at the growth temperature, and at low water contents a cubic liquid crystalline phase at 58°C. The ratio iso/ante-iso acyl chains was 0.3 in this lipid. PE isolated from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The molar ratio of iso/anteiso acyl chains increases more than 20-fold when the growth temperature is raised from 20 to 55 °C. This result agrees with previous observations (Rilfors et al, 1978(Rilfors et al, , 1982; however, in the present PE preparations, the increase in the acyl chain ratio is somewhat more pronounced. PE-55 does not contain any unsaturated acyl chains, while PE-20 contains about 21 mol % of monounsaturated chains (Table 1).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The molar ratio of iso/anteiso acyl chains increases more than 20-fold when the growth temperature is raised from 20 to 55 °C. This result agrees with previous observations (Rilfors et al, 1978(Rilfors et al, , 1982; however, in the present PE preparations, the increase in the acyl chain ratio is somewhat more pronounced. PE-55 does not contain any unsaturated acyl chains, while PE-20 contains about 21 mol % of monounsaturated chains (Table 1).…”
Section: Discussionsupporting
confidence: 94%
“…temperature is raised from 50 to 55 °C, the 31P NMR spectra show an increasing fraction of a narrow symmetrical signal in addition to the anisotropic spectral component. At such a low water content as 3 mol of 2H2G/mol of lipid, the narrow signal represents a reversed cubic liquid-crystalline (I2) phase (Rilfors et al, 1982;Eriksson et al, 1985a;Sjolund et al, 1987;Lindblom & Rilfors, 1989), and it was shown in earlier studies that this cubic phase is bicontinuous and belongs to the space group laid (Rilfors et al, 1982;Lindblom & Rilfors, 1989). Thus, an La phase and an I2 phase are in equilibrium between 50 and 55 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the phase boundaries are deter-phosphatidylcholine/bile salt (BS) mixtures (4, 5, 10, 13, mined by the spontaneous curvature of the monolayers. We show 14), the kinetics and mechanisms of phase transformation that because the phase boundaries are apparently independent of (12, 15,16), the nature of the interactions in these systems ionic strength, the influence of ionic strength on the spontaneous (10,(17)(18)(19), and the structure of the PC/BS mixed assemcurvature is negligible in comparison to the main value determined blies (11,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Yet, several basic issues remain unclear Key Words: phospholipids; bile salts; vesicles; mixed micelles; fect both the phase behavior of the mixed systems and the ionic strength.…”
mentioning
confidence: 98%